2018
DOI: 10.3892/ijmm.2018.3968
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tetramethylpyrazine and hyperlipidemia on hepcidin homeostasis in mice

Abstract: Iron homeostasis is strictly regulated in mammals, and disordered iron metabolism is recognized as a risk factor for various diseases, including cardiovascular disease. The hepcidin-ferroportin axis is the key signaling mechanism that controls systemic iron homeostasis. Increased serum hepcidin is associated with multiple types of cancer and atherosclerosis (AS), and therapeutics that decrease hepcidin levels have been proposed to treat these diseases. However, the effects of abnormal circulating hepcidin on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Moreover, hepcidin is a hormonal regulator of iron homeostasis. Zhang et al ( 135 ). found that the serum hepcidin was elevated in a hyperlipidemia model, which suggests the iron burden in hyperlipidemia may be connected to an unbalanced hepcidin-FPN axis.…”
Section: Ferroptosis and Metabolic Syndrome And Complicationsmentioning
confidence: 99%
“…Moreover, hepcidin is a hormonal regulator of iron homeostasis. Zhang et al ( 135 ). found that the serum hepcidin was elevated in a hyperlipidemia model, which suggests the iron burden in hyperlipidemia may be connected to an unbalanced hepcidin-FPN axis.…”
Section: Ferroptosis and Metabolic Syndrome And Complicationsmentioning
confidence: 99%